Susceptibility of some new strawberry genotypes to infestation by western flower thrips, Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae) in the nursery - Eman M. Abdelmaksoud; Shoukry A. El-Refai; Kadry W. Mahmoud; Mohamed E. Ragab (Annals of Agricultural Sciences, 2020)
Strawberries are infested with Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae) in Egypt. This study evaluated the effects of the biochemical components and leaf surface characteristics of ten new strawberry cultivars (Fortuna, Festival, Sahary, Forintaris, Red Merlin, Winter Star, Winter Dawn, Eliana, Montary and Florida) on the levels of infestation by F. occidentalis. There were significant differences in the susceptibility of strawberry cultivars to infestation by F. occidentalis. Fortuna, Sahary, Festival and Forntaris were the most susceptible cultivars. Red Merlin, Winter Star, Winter Dawn and Eliana had intermediate infestations. Montary and Florida were the most resistant cultivars. The relationship between mean number of F. occidentalis and leaf nitrogen was not significant. There was a significant relationship between mean numbers of F. occidentalis and phosphorus, potassium and total phenols content of leaves. The highest mean numbers of F. occidentalis were found on leaves of the Fortuna cultivar with high levels of phosphorus and low levels of potassium and total phenol. The lowest mean numbers of F. occidentalis were found on the leaves of the Montary and Florida cultivars with low levels of phosphorus and high levels of total phenols and potassium. Cultivars with higher density of non-glandular trichomes had significantly fewer F. occidentalis than cultivars with lower densities of non-glandular trichomes on the upper leaf surface. Similarly, cultivars with thicker leaves had significantly fewer thrips than cultivars with thinner leaves. The proper choice of strawberry cultivar is an important component of integrated pest management programs for controlling thrips in strawberry nurseries.